Study on the effect of iron-based deoxidizing inhibitors for coal spontaneous combustion prevention - Hao, C.; Chen, Y.; Wang, J.; Deng, C.; Xu, Guang; Dai, F.; Si, R.; Wang, H.; Wang, H. (M D P I AG, 2018)
To improve the prevention of spontaneous coal combustion, reduced iron powder and other ingredients should be added together to form an iron-based deoxidizing inhibitor, with the dual effect of oxygen consumption and inhibition. The oxygen consumption rate of the inhibitor was studied through experiments. According to the theory of coordination resistance, the coordination resistance of Fe 3+ was studied via the density functional method. Subsequently, a comparative experiment of the effects on spontaneous coal combustion was conducted. The research shows that several kinds of common resistance agents that are added to the reduced iron powder can consume oxygen. However, the rate of oxygen consumption varies. Fe 3+ produced by the reduced iron powder indicates a strong coordination resistance. When compared with traditional inhibitors of Mg 2+ , Fe 3+ has a stronger inhibition effect on the N, P, and S reactive groups in coal. The overall inhibitory effect is better than that of traditional inhibitors, because of the increased oxygen consumption and the coordination resistance of Fe 3+ on the basis of traditional inhibitors.